Efficacy and safety of abatacept in active primary Sjögren's syndrome: results of a phase III, randomised, placebo-controlled trial. Issue 3 (9th November 2020) - Baer, Alan N; Gottenberg, Jacques-Eric; St Clair, E William; Sumida, Takayuki; Takeuchi, Tsutomu; Seror, Raphaèle; Foulks, Gary; Nys, Marleen; Mukherjee, Sumanta; Wong, Robert; Ray, Neelanjana; Bootsma, Hendrika
Abstract : Objectives: To evaluate efficacy and safety of abatacept in adults with active primary Sjögren's syndrome (pSS) in a phase III, randomised, double-blind, placebo-controlled trial. Methods: Eligible patients (moderate-to-severe pSS [2016 ACR/European League Against Rheumatism (EULAR) criteria], EULAR Sjögren's Syndrome Disease Activity Index [ESSDAI] ≥5, anti-SS-related antigen A/anti-Ro antibody positive) received weekly subcutaneous abatacept 125 mg or placebo for 169 days followed by an open-label extension to day 365. Primary endpoint was mean change from baseline in ESSDAI at day 169. Key secondary endpoints were mean change from baseline in EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI) and stimulated whole salivary flow (SWSF) at day 169. Other secondary clinical endpoints included glandular functions and patient-reported outcomes. Selected biomarkers and immune cell phenotypes were examined. Safety was monitored. Results: Of 187 patients randomised, 168 completed double-blind period and 165 continued into open-label period. Mean (SD) baseline ESSDAI and ESSPRI total scores were 9.4 (4.3) and 6.5 (2.0), respectively. Statistical significance was not reached for primary (ESSDAI −3.2 abatacept vs −3.7 placebo, p=0.442) or key secondary endpoints (ESSPRI, p=0.337; SWSF, p=0.584). No clinical benefit of abatacept over placebo at day 169 was seen with other clinical and PRO endpoints. Relative to baseline, abatacept was associated with significant differences vs placebo in some disease-relevant biomarkers (including IgG, IgA, IgM-rheumatoid factor) and pathogenic cell subpopulations (post hoc analyses). No new safety signals were identified. Conclusions: Abatacept treatment did not result in significant clinical efficacy compared with placebo in patients with moderate-to-severe pSS, despite evidence of biological activity.